Political elitism: obstacle to or opportunity for socio-economic expansion and total independence of Africa? the case of the Democratic Republic of the Congo - Mbecke, P. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The failure of most African states to achieve their total independence forms a remarkable theme in the post-colonial globalisation debate. Critics reflect how globalisation has benefited the first world countries through the burden of their capitalist free market economic system coupled with state capture cases by multinational corporations and the policies of the institutions of Bretton Woods to the detriment of under-developed countries. Although all African countries have accessed their political independences, it is a fact that their social and economic expansion and their total independence are yet to be materialised. This paper, refers to the case of the Democratic Republic of Congo to observe that, at international level, Africa is a victim of the current westernised globalisation and that, political elitism has been an obstacle – rather than an opportunity for the attainment of socio-economic expansion and total independence. Using an exploratory and conceptual research approach, the paper reviews the elitist paradigm and the elite theory and analyses the characteristics of the African political elites with regard to their political and socio-economic development roles as well as their relationship with the masses. Through public an administration research methodology, the paper proposes a conceptual understanding of political elitism to guide a conclusive research on how African political elites can facilitate the socio-economic and total independence of Africa for the continent to equally enjoy the rewards of globalisation as the developed nations.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: African political elites; Democratic Republic of Congo; Elite theory; Elitism; Political elites; Socio-economic expansion; Total independence; Elite (Social sciences); Autonomy